Assessing genomics confidence and learning needs in Australian nurses and midwives: an educational program evaluation - Alexander, Kim E.; Rolfe, Melanie; Gabbett, Michael T. (Frontiers in Genetics, 2024)
Introduction: The mainstreaming of genomics across healthcare specialties necessitates that all nurses and midwives have a high literacy in genomics. Methods: We aimed to design, develop, implement and evaluate a genomics education workshop for nurses and midwives using action research principles. Results: Registered nurses and midwives completed an online survey regarding genomics confidence and learning needs (n = 274). The results of this survey were used to develop the genomics education workshop. The workshop was run three times (n = 105) with evaluation data being collected both before and after each workshop. Significant improvements in confidence across all learning domains was found following the workshops (p < 0.001). A desire for more education across all learning domains except for genetics knowledge was also identified (p < 0.001). Discussion: Genomics education workshops were found to increase the confidence of nurses and midwives across a range of specialties. Nurses and midwives also expressed a desire for further education in genomics.